2019
DOI: 10.1109/tbme.2018.2884129
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Diffusion Map Based Fusion of Multimodal Brain Connectivity Networks for IQ Prediction

Abstract: Objective: To explain individual differences in development, behavior, and cognition, most previous studies focused on projecting resting-state functional MRI (fMRI) based functional connectivity (FC) data into a low-dimensional space via linear dimensionality reduction techniques, followed by executing analysis operations. However, linear dimensionality analysis techniques may fail to capture nonlinearity of brain neuroactivity. Moreover, besides resting-state FC, FC based on task fMRI can be expected to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…In Qin et al () and Kashyap et al (), they decomposed RSFC (or timecourse) to extract individual‐specific RSFC (or timecourse) with different methods, which obtained obvious improvements in prediction. The second way is to combine various kinds of information with RSFC to enhance the prediction, such as task‐fMRI based FC (Elliott et al, ; Gao et al, ; Xiao, Stephen, Wilson, Calhoun, & Wang, ) and dynamic FC (Liegeois et al, ; Lim et al, ; Park et al, ), which could provide complementary information to the conventional FC. The third way is to decrease the influence of the possible noise in rs‐fMRI signal, for instance, the global signal regression (Li et al, ) and motion artifact correction (Nielsen et al, ) have been reported to advance the RSFC‐behavior prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In Qin et al () and Kashyap et al (), they decomposed RSFC (or timecourse) to extract individual‐specific RSFC (or timecourse) with different methods, which obtained obvious improvements in prediction. The second way is to combine various kinds of information with RSFC to enhance the prediction, such as task‐fMRI based FC (Elliott et al, ; Gao et al, ; Xiao, Stephen, Wilson, Calhoun, & Wang, ) and dynamic FC (Liegeois et al, ; Lim et al, ; Park et al, ), which could provide complementary information to the conventional FC. The third way is to decrease the influence of the possible noise in rs‐fMRI signal, for instance, the global signal regression (Li et al, ) and motion artifact correction (Nielsen et al, ) have been reported to advance the RSFC‐behavior prediction.…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that the correlation between brain size and neuron number across species is, while present, fairly variable (Herculano-Houzel et al, 2014). Further, the number of neurons, while important, is no more (and possibly less) important than the patterns of connections between those neurons and the regions they compose (e.g., in humans, Emerson and Cantlon, 2012;Xiang et al, 2012;Xiao et al, 2018). Here, research into marine mammal neurobiology is still in its infancy.…”
Section: The Brainmentioning
confidence: 99%
“…A number of studies have leveraged the power of ML methods to build flexible nonlinear mapping models and use them to identify neural correlates of brain disorders (e.g., Hasanzadeh et al, 2019;Kazemi & Houghten, 2018;Kim et al, 2016;Leming et al, 2020) and behavioral traits (e.g., Kumar et al, 2019;Morioka et al, 2020;Xiao et al, 2019). Yet the vast majority of cognitive neuroscience studies use linear mapping models (such as linear regression), resulting in a gap between different neuroscience subfields.…”
Section: The Controversymentioning
confidence: 99%
“…The concurrent increase in the size of available datasets (e.g., Chang et al, 2019;Majaj et al, 2015;Schoffelen et al, 2019) has enabled researchers to train large-scale mapping models without overfitting them. As a result, a number of applied neuroscience studies have leveraged the power of ML-based methods to build flexible nonlinear mapping models and use them to identify neural correlates of brain disorders (e.g., Hasanzadeh et al, 2019;Kazemi & Houghten, 2018;Kim et al, 2016;Leming et al, 2020) and of behavioral traits (e.g., Kumar et al, 2019;Morioka et al, 2020;Xiao et al, 2019).…”
Section: The Controversymentioning
confidence: 99%